IN THE ARENA OF IDEAS: WOKE CULTURE, SOCIAL JUSTICE, AND RIGHT-WING POPULISM" - admin, João Miguel (American Journal of Legal Practice (AJLP), 2023)
This paper explores the impact of Communist infiltration in public institutions and dissemination of Marxist ideas on the emergence of Woke Culture, Social Justice Warriors, and the resurgence of Right-Wing conservatism across the Western World. The authors argue that the Stalinist regimes' failure to establish a World Socialist Republic in the 20th century led to a new strategy of using Critical Theory and Postmodernism to subvert Western cultural values and replace them with their own. The Frankfurt School and other Neo-Marxist intellectuals aimed to dismantle Western culture and create a counterculture that would empower Woke Culture and give rise to Social Justice Warriors. This strategy has resulted in the politicization of identity groups and the emergence of a generation of young people who prioritize social justice over personal responsibility, thereby creating a breeding ground for Right-Wing conservatism. As a response, religious and conservative parties have risen to contain the spread of Neo-Marxist ideas. The article explores the Frankfurt School's role in attacking Western culture and the theoretical crisis of Marxism and the creation of Communist International. The paper concludes by emphasizing the role of ideology in shaping contemporary politics and culture. The authors argue that the rise of Woke Culture and Right-Wing conservatism reflects the ongoing conflict between Marxist and conservative ideologies, which will continue to shape political discourse in the Western World.